Anti-acne and Tyrosinase Inhibition Properties of Taxifolin and Some Flavanonol Rhamnosides from Kempas (Koompassia malaccensis) - Irmanida Batubara; Harlinda Kuspradini; Tohru Mitsunaga (Masyarakat Peneliti Kayu Indonesia, 2010)
Taxifolin (1) and some flavanonol rhamnosides (neoastilbin (2), astilbin (3), and isoastilbin (4)) have been isolated from kempas (Koompassia malaccensis). Our previous research about antimicrobial activity against Streptococcus sobrinus and glucosyltransferase inhibitory activity of these compounds have been reported. Now, we carried out the anti-acne and tyrosinase inhibition properties of all four compounds. Antimicrobial against Propionibacterium acnes, P. acnes lipase inhibitory activity and antioxidant activity were established for anti-acne activity. Tyrosinase inhibition property was measured using L-tyrosine and L-DOPA as substrate. The results for anti-acne showed that no antimicrobial activity against P. acnes for all compounds, the best lipase inhibition properties showed on compound 4 with IC50 about 1.36 mg/ml, and % inhibition for antioxidant at concentration 10 mg/ml are 31.16, 25.64, 28.47, and 31.01% respectively. Tyrosinase inhibition of compound 1 at concentration 1 mg/ml is 24.12% for monophenolase and 5.18% for diphenolase. Compound 2 has tyrosinase inhibition about 25.95% (monophenolase) and 14.18% (diphenolase) at concentration 1 mg/ml. Compound 3 has tyrosinase inhibition about 27.17% (monophenolase) and 6.23% (diphenolase) at same concentration, while compound 4 has tyrosinase inhibition about 11.17% (monophenolase) and 9.75% (diphenolase).